2005
DOI: 10.1002/chin.200530022
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Hydrogen in Protonic Chabazite.

Abstract: Sorption G 6000Liquid Hydrogen in Protonic Chabazite. -Hydrogen adsorption in a series of zeolites is characterized by volumetric techniques and IR spectroscopy at 15 K. In H-SSZ-13 zeolite the cooperative role played by high surface area, internal wall topology, and presence of high binding energy sites (protons) allows hydrogen to become densified inside the nanopores at favorable temperature and pressure conditions. The H-SSZ-13 zeolite is a promising material for efficient hydrogen storage. -(ZECCHINA, A.;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…An average BE (4.5 kJ/mol) resulted for H 2 interacting with H-O1, H-O2 and H-O4 cases, whereas H-O3 showed a much lower BE value. These computed BE values are about half than the experimental estimate of 9.7 kJ/mol obtained by means of variable-temperature FTIR spectroscopy [10]. This may be due to dispersive contributions not accounted for by the B3LYP functional.…”
Section: H 2 In Proton-exchanged Chabazitesmentioning
confidence: 76%
See 3 more Smart Citations
“…An average BE (4.5 kJ/mol) resulted for H 2 interacting with H-O1, H-O2 and H-O4 cases, whereas H-O3 showed a much lower BE value. These computed BE values are about half than the experimental estimate of 9.7 kJ/mol obtained by means of variable-temperature FTIR spectroscopy [10]. This may be due to dispersive contributions not accounted for by the B3LYP functional.…”
Section: H 2 In Proton-exchanged Chabazitesmentioning
confidence: 76%
“…Table 3 also shows a sensible decrease of the H 2 Do 01 shifts upon improving the basis set for the B3LYP periodic cases. Comparison with the experimental shifts of the H-H stretching frequency of H 2 adsorbed on HCHA-11/1 [10] (see Table 1), shows that all the computed frequency shifts are underestimated.…”
Section: H 2 In Proton-exchanged Chabazitesmentioning
confidence: 85%
See 2 more Smart Citations
“…A general chemical formula of zeolites is represented as Recent studies have shown that zeolites can be potential materials for reversible hydrogen storage [6][7][8][9][10][11][12][13][14][15]. Du and Wu reported hydrogen adsorption capacity of 2.55 wt% for NaX at 77 K and 70 bar pressure [7].…”
Section: Introductionmentioning
confidence: 99%